2022
DOI: 10.1002/solr.202200881
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Sulfur Defect Rich ZnIn2S4/SnSe2 Photocatalyst with Ohmic Junction for Efficient Water to Hydrogen Energy Conversion

Abstract: The development of a noble‐metal‐free cocatalyst is of great significance for boosting photocatalytic H2 evolution performance. Herein, SnSe2 is developed as a cocatalyst to in situ attachment on the surface of sulfur defect rich ZnIn2S4 (Vs‐ZIS) via a simple hydrothermal method. Owing to the intimate atomic‐level interface and the different work function between Vs‐ZIS and SnSe2, a particular Ohmic junction with internal electric field is formed in Vs‐ZIS/SnSe2, which facilitates the electrons in Vs‐ZIS trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The EPR spectra were recorded to further verify if V S were successfully introduced into the ZIS-V S and ZIS-V S /BMO samples. As shown in Figure d, the above samples display typical single Lorentzian lines in the same magnetic field region with a g -value of 2.007, which could be attributed to the unpaired electrons on the sulfur atoms . The ZIS sample presented a weak EPR signal response.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The EPR spectra were recorded to further verify if V S were successfully introduced into the ZIS-V S and ZIS-V S /BMO samples. As shown in Figure d, the above samples display typical single Lorentzian lines in the same magnetic field region with a g -value of 2.007, which could be attributed to the unpaired electrons on the sulfur atoms . The ZIS sample presented a weak EPR signal response.…”
Section: Resultsmentioning
confidence: 85%
“…As shown in Figure 1d, the above samples display typical single Lorentzian lines in the same magnetic field region with a g-value of 2.007, which could be attributed to the unpaired electrons on the sulfur atoms. 17 The ZIS sample presented a weak EPR signal response. In comparison, the EPR peaks centered at g = 2.007 presented significant enhancement in the ZIS-V S and ZIS-V S /BMO samples, revealing the significantly increased sulfur vacancy concentration in those samples.…”
Section: Resultsmentioning
confidence: 97%
“…These defects in photocatalytic hybrid materials might be point defects, volume defects, or the terminations of line defects and planar defects, similar to the surface defects. 44 Defect-engineered photocatalysts have been widely used in various photocatalytic applications such as organic pollutants' degradation, 56,57 pharmaceutical degradation, 58,59 CO 2 reduction, 60,61 H 2 evolution, 62,63 N 2 reduction, 64,65 etc. which directly focus on environmental remediation and sustainability, providing a large scope of development of defect engineering in materials.…”
Section: Basic Understanding and Types Of Defectsmentioning
confidence: 99%
“…It has been reported that metal selenides could accelerate the charge transfer of the hydrogen evolution reaction due to their lower electrical resistance, indicating that metal selenides are promising catalysts. 6,26,27 Recently, it was reported that metal selenides ZnSe, 28 SnSe 2 , 29 NiSe 2 , 16 and MoSe 2 30 were used to form composites with ZnIn 2 S 4 to promote charge migration, thus improving the activity of photocatalytic hydrogen evolution. The inherent properties of CoSe 2 endowed it with high electronic conductivity and proton adsorption ability, while its low cost and stable chemical properties made it a potential substitute for noble metals.…”
Section: Introductionmentioning
confidence: 99%